Permissible collateral and access to finance: Evidence from a quasi-natural experiment - Bing Xu (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
By allowing large classes of movable assets to be used as collateral, the Property Law reform trans-formed the secured transactions in China. Difference-in-differences tests show firms operating with ex-ante more movable assets expand access to bank credit and prolong debt maturity. However, the reform does not seem to improve the efficiency of credit allocation, as debt capacity of ex-ante low quality firms expands the most following the reform. Credit expansion also does not lead to better firm performance. These findings are not driven by confounding factors such as improvements in creditor and property rights protection. Our results also cannot be explained by other important reforms which were introduced around the same time as the introduction of the Property Law. These include anti-tunneling and split-share reforms and amendments to the corporate tax structure in China. We conduct explicit robustness tests for these other reforms and amendments to the corporate tax structure in China. We conduct explicit robustness tests for these other reforms and hence contribute to the empirical literature on the reform process in China with new findings.
URN:NBN:fi:bof-201801311153
Keywords: G21; G28; G32; K22; 330